ISOLASI DAN KARAKTERISASI Beauveria bassiana SEBAGAI FUNGI ANTI HAMA - Eka Sari; Zulvia Intan Sari; Anggi Nico Flatian; Eman Sulaeman (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
Development of biological potential could to be a solution of pest problems and environmental damage by pesticides. One of the organisms that are currently often be used for biopesticides is the entomopathogenic fungi such as Beauveria brassiana. This study aim to isolate, characterize of pest-resistant fungi and apply it to some agricultural insect pests in vitro. Samples which used were planthoppers, aphids, grasshoppers and isolated fungi Beauveria bassiana from Biogen Laboratory. The research was conducted in Soil and Environmental Biotechnology Laboratory, Dramaga, Bogor. Isolation method with Insect Bait Methode. Isolation and characterization of pest-resistant fungi that are planthoppers and aphids show the result that the great possibilities are the Beauveria bassiana fungus, that is clearly visible from the obtained physical characteristics, the white and sealed hyphae and conidia round oval. In addition, the fungi which used is a pathogenic fungi on the pest of aphids, planthoppers, and grasshoppers.